2019
DOI: 10.3390/toxins11120700
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Application of a Qatari Burkholderia cepacia strain (QBC03) in the Biocontrol of Mycotoxigenic Fungi and in the Reduction of Ochratoxin A biosynthesis by Aspergillus carbonarius

Abstract: Mycotoxins are secondary metabolites produced by certain filamentous fungi, causing human and animal health issues upon the ingestion of contaminated food and feed. Among the safest approaches to the control of mycotoxigenic fungi and mycotoxin detoxification is the application of microbial biocontrol agents. Burkholderia cepacia is known for producing metabolites active against a broad number of pathogenic fungi. In this study, the antifungal potential of a Qatari strain of Burkholderia cepacia (QBC03) was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In addition, GC×GC-TOFMS results show that the production of fatty acids such as linoleic, Fungal melanin has attracted interest due to its potential usage in many industries including nanotechnology, biomedicine, dermo-cosmetics, and materials science [56]. However, Aspergillus carbonarius is also known as a producer of ochratoxin A (OTA) [74]. For this reason, further research on melanin production, OTA level and physical OTA removal methods such as filtration and pressure needs to be undertaken.…”
Section: Characterization Of Fungal Biomassmentioning
confidence: 99%
“…In addition, GC×GC-TOFMS results show that the production of fatty acids such as linoleic, Fungal melanin has attracted interest due to its potential usage in many industries including nanotechnology, biomedicine, dermo-cosmetics, and materials science [56]. However, Aspergillus carbonarius is also known as a producer of ochratoxin A (OTA) [74]. For this reason, further research on melanin production, OTA level and physical OTA removal methods such as filtration and pressure needs to be undertaken.…”
Section: Characterization Of Fungal Biomassmentioning
confidence: 99%
“…The results indicated that QBC03 culture supernatant acted inhibitory to the growth of Aspergillus carbonarius , Fusarium culmorum , and P. verrucosum . Synthesis of ochratoxin A by A. carbonarius was also reduced [ 168 ]. De Melo Nazareth et al reported that Lactobacillus plantarum CECT 749 CFS showed a high antifungal effect against A. flavus and F. verticillioides on corn kernels and corn ears, and FB1 and AFB1 levels were significantly reduced [ 169 ].…”
Section: Bio-acceptable Solutions For Fungal Control and Detoxification Of Mycotoxinsmentioning
confidence: 99%
“…Bacteria [162][163][164][165][166][167][168][169][170][171] Yeast [172][173][174][175][176][177][178] Fungi [1,163,179,180] Commercial agents [181] Preharvest agronomical strategies Agro-technical measures…”
Section: Microbiological Approach Microorganismsmentioning
confidence: 99%
“…Biotechnological strategies are widely used in eliminating OTA because it is environmentally friendly and effective. Several biocontrol strains like Burkholderia cepacia , Brevibacterium casei , Aspergillus niger , and Alcaligenes faecalis were researched and evaluated with varying degrees of success [ 20 , 21 , 22 , 23 , 24 ]. The direct degradation of OTA to a less toxic substance ochratoxin α (OTα) is the most significant mechanism [ 22 ], but some microorganisms can also have antifungal properties and inhibit OTA production [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%